Grammarly as AI-powered English Writing Assistant: Students’ Alternative for Writing English - Tira Nur Fitria (Metathesis: Journal of English Language, Literature, and Teaching, 2021)
The presence of ‘Grammarly’ as one of the online grammar checkers as the impact of technology development.  This paper aims to reveal an overview of ‘Grammarly’ as an AI-powered English Writing Assistant for EFL students in Writing English. This research applies descriptive qualitative research. Based on the analysis, using Grammarly software shows the performance increased. Before using Grammarly, the performance of the test score is 34 out of 100. After using Grammarly, the performance text score is 77 out of 100. This score shows the quality of writing in this text increased. The performance can be increased based on Grammarly's suggestions in a Premium account. The researcher recommends the students to use Grammarly. Grammarly is a web tool to perform grammar checks well, starting from the spelling of words, sentence structure to standard grammar. Grammarly is free, so it is recommended for students who want to check various documents or articles in English. Grammarly helps check the grammatical rule, the spelling rule in English structure, also correct errors in writing such as punctuation and capitalization. Grammarly runs on an Artificial Intelligence (AI) system, which is built to analyze English sentences relying on a set of rules. Grammarly takes context when showing corrections or suggestions, and inform the students quickly but still precisely. For accuracy, two service options available both free and paid features. Of course, the Grammarly free version still has limitations and in-service features, unlike the paid version (premium) which has full advantages and benefits, many features, and complete.